Between Transparency and Effectiveness: Accountability in Improving the Quality of Administrative Services at the Population and Civil Registration Office Bone Regency - HM, Syarifuddin; Bardi, Nur Khafifah; A, M. Awaluddin; Asdar, Muhammad; Triadi, Feby (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2025)
Public service is a key indicator of government performance directly felt by the public, yet in practice, many fundamental problems remain, including in population administration services at the Bone Regency Population and Civil Registration Office (Disdukcapil). This study aims to analyze the application of accountability principles in population administration services and to formulate strategies that can improve the quality and legitimacy of public services in the region. Using a qualitative approach with a case study design, data were collected through observation, in-depth interviews, and documentation studies, then analyzed using triangulation and pattern matching techniques. The results show that the Bone Disdukcapil has implemented several innovations, such as service digitization, sub-district-based programs, information transparency, and the operation of the Public Service Mall. However, various obstacles remain, including limited digital infrastructure, low public technological literacy, scarcity of ID forms, limited number of officers, and suboptimal participatory complaint and evaluation mechanisms. These findings indicate that public service accountability strategies are still top-down and need to be reformulated with an emphasis on community participation, transparency, and cross-actor collaboration. This study concludes that strengthening human resource capacity, improving digital infrastructure, strengthening formal complaint channels, and implementing participatory evaluation mechanisms are key to building more inclusive, transparent, and accountable population administration services in Bone Regency